A comparison of male and female student issues that affect enrollment and retention in electronics and computer engineering technology programs at a for-profit institution - Agajanian, Aram, author; Timpson, William M., advisor; Morgan, George A., advisor; Wallner, Barbara K., committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2005)
The objective of this dissertation was to compare men and women in terms of variables related to enrollment and retention issues in electronics and computer engineering technology programs at DeVry University's Chicago area campuses. The study used 2 x 3 factorial ANOVA and multiple regression in order to analyze the quantitative data. Surveys were administered to 576 students in electronics programs at DeVry University's Chicago and Tinley Park campuses in the fall 2004 trimester. The response rate was 63.9%. The survey instrument asked for information on the 11 dependent variables, gender, program level, and age. The instrument also asked two open-ended questions about students' pre-college mathematics/science and electronics interests and how DeVry experience impacted them. The results revealed that females had significantly lower ratings than males in terms of: (a) self-confidence, (b) pre-college encouragement, (c) pre-college consideration to apply for electronics, and (d) household income. Statistical analyses also indicated significant differences for program level in regard to: (a) satisfaction with electronics programs and (b) pre-college encouragement. Significant interactions of gender and program level were found in terms of parents' education and pre-college encouragement. Multiple regression analysis indicated that self-confidence; approachability, concern, and fairness of the electronics professors; female gender; and beginning program level combine to be significant predictors of satisfaction with electronics programs. The findings generally agreed with the literature review that females had significantly lower ratings than males in regard to the following: (a) self-confidence, (b) pre-college encouragement, and (c) pre-college consideration to apply for electronics programs. In general, the results supported recent previous literature that there were no significant differences between males and females in terms of: (a) pre-college mathematics/science interest and grades and (b) years of mathematics/science in high school. The results generally did not support the previous literature that females report significantly lower ratings than males in regard to: (a) self-efficacy, (b) professors' approachability, concern, and fairness, and (c) satisfaction with electronics programs. The findings generally did not agree with the literature review that females rate professors' use of teamwork significantly more helpful than males. The study concludes that lack of pre-college encouragement seems to be the most important reason for low female enrollment in electronics programs at DeVry and recommends ways to increase pre-college encouragement.
Keywords: higher education; vocational education; women's studies